2022
DOI: 10.1002/cpe.7353
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid meta‐heuristic algorithm for optimal virtual machine placement and migration in cloud computing

Abstract: Data sharing in cloud computing happens with multiple participants to freely distribute the group data, which focuses on advancing the effectiveness of work in cooperative backgrounds and has attained widespread benefits. The main intent of this article is to accomplish a virtual machines (VMs) placement and migration model using a hybrid meta-heuristic concept. A new meta-heuristic algorithm named DJ-HA is developed for optimal VM placement and migration to reduce the count of active servers, and minimization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
(60 reference statements)
0
0
0
Order By: Relevance
“…The comparison between Balanced-DRL and some typical works in related research in terms of field, problem type, approach, and achievements is shown in Table 6. The papers [10,16,19,22] focus on optimizing job allocation in cloud computing platforms. Each paper proposes optimization algorithms with varying key performance indicators, such as latency and energy consumption, while employing different types of algorithms.…”
Section: Comparison Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparison between Balanced-DRL and some typical works in related research in terms of field, problem type, approach, and achievements is shown in Table 6. The papers [10,16,19,22] focus on optimizing job allocation in cloud computing platforms. Each paper proposes optimization algorithms with varying key performance indicators, such as latency and energy consumption, while employing different types of algorithms.…”
Section: Comparison Discussionmentioning
confidence: 99%
“…By maximizing resource utilization using three stages-parallelization, task allocation, and task redistribution-the algorithm aims to provide better services. Infantia et al [16] proposed a novel meta-heuristic algorithm for virtual machine (VM) placement and migration in cloud environments, aiming to achieve optimal VM placement and migration, reduce the number of active servers, and minimize completion time and energy consumption. Ghobaei-Arani et al [17] proposed an efficient IoT service deployment solution based on the whale optimization algorithm to address the deployment problem of IoT applications in fog computing.…”
Section: Job Allocation Algorithms For Traditional Data Centersmentioning
confidence: 99%
“…Many researchers have explored the many-objective loadbalancing optimization problem using swarm intelligence algorithms based on the population in the IoT, which has generated a set of optimized solutions. Researchers have gradually improved/combined evolutionary algorithms to achieve load-balancing techniques to have optimal QoS and performance with several objectives [28], [35]. Also, A divide-and-conquer optimization method has been performed for complex problems to facilitate finding the best solutions [44].…”
Section: Figure 2 the General Framework Of Multi-direction Qosmentioning
confidence: 99%
“…To protect data from being accessed without authorization and to verify that the data have not been tampered with, a plan has been developed that, in addition to resolving the issues of privacy and consistency, also addresses the issue of unauthorized access. The author of article [10] suggested a hybrid technique called PHECC (Polynomial-based Hashing and Elliptic Curve Cryptography). This approach combines PH with ECC security procedures in order to guarantee the customers that users' data will be secure while they are stored on the cloud.…”
Section: Related Studymentioning
confidence: 99%